Clinicians in 25 countries prefer to use lower levels of oxygen to resuscitate preterm infants at birth. (24th June 2016) - Oei, Ju Lee; Ghadge, Alpana; Coates, Elisabeth; Wright, Ian M.; Saugstad, Ola D.; Vento, Maximo; Buonocore, Giuseppe; Nagashima, Tatsuo; Suzuki, Keiji; Hosono, Shiguhero; Davis, Peter G.; Craven, Paul; et al.
Abstract: Aim: This study determined current international clinical practice and opinions regarding initial fractional inspired oxygen (FiO2 ) and pulse oximetry (SpO2 ) targets for delivery room resuscitation of preterm infants of less than 29 weeks of gestation. Methods: An online survey was disseminated to neonatal clinicians via established professional clinical networks using a web‐based survey programme between March 9 and June 30, 2015. Results: Of the 630 responses from 25 countries, 60% were from neonatologists. The majority (77%) would target SpO2 between the 10th to 50th percentiles values for full‐term infants. The median starting FiO2 was 0.3, with Japan using the highest (0.4) and the UK using the lowest (0.21). New Zealand targeted the highest SpO2 percentiles (median 50%). Most respondents agreed or did not disagree that a trial was required that compared the higher FiO2 of 0.6 (83%), targeting the 50th SpO2 percentile (60%), and the lower FiO2 of 0.21 (80%), targeting the 10th SpO2 percentile (78%). Most (65%) would join this trial. Many considered that evidence was lacking and further research was needed. Conclusion: Clinicians currently favour lower SpO2 targets for preterm resuscitation, despite acknowledging the lack of evidence for benefit or harm, and 65% would join a clinical trial.